1995
DOI: 10.1017/s0022112095000255
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation for flow past a cylinder between parallel planes

Abstract: Numerical experiments are described to ascertain how the steady flow past a circular cylinder loses stability as the Reynolds number is increased. A novel feature of the present study is that the cylinder is confined between parallel planes, allowing a more definitive specification of the flow, both experimentally and computationally, than is possible for the unbounded case. Since the structure of the bifurcation is unclear from the extant literature, with the experimental and computational evidence not in goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
2
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 16 publications
13
80
2
2
Order By: Relevance
“…Figure ll For a fixed twodimensional cylinder embedded in a Poiseuille flow, St was observed to increase even more strongly with S, becoming three times larger ヲ ッ イ s セ @ 0.5 than in the unconfined case (Chen et al 1995;Sahin & Owens 2004).…”
Section: 1 Frequency Of the Periodic Pathmentioning
confidence: 91%
See 1 more Smart Citation
“…Figure ll For a fixed twodimensional cylinder embedded in a Poiseuille flow, St was observed to increase even more strongly with S, becoming three times larger ヲ ッ イ s セ @ 0.5 than in the unconfined case (Chen et al 1995;Sahin & Owens 2004).…”
Section: 1 Frequency Of the Periodic Pathmentioning
confidence: 91%
“…Below the threshold of wake instability, Tavener (1994) and Maheshwari, Chhabra & Biswas (2006) have shown that the length of the recirculating wake of a fixed sphere decreases when the confinement ratio is increased. Numerical investigations for fixed two-dimensional cylinders (Chen, Pritchard & Tavener 1995 ;Sahin & Owens 2004) and fixed spheres (Tavener 1994;Cliffe, Spence & Tavener 2000) placed in an incoming confined flow indicate that for S < 0.5, wake instability is delayed. For 0.5 < S < 0.7, the threshold for wake instability decreases but remains larger than its value in the unconfined case.…”
Section: Introductionmentioning
confidence: 99%
“…(10), u is the vertical component of the velocity field specified on the upstream boundary and u D is the average longitudinal velocity based on the diameter of the semicylinder. The accuracy of the numerical algorithm was tested by comparing results of the mean Nusselt number against available analytical [2] and numerical results [35] for the standard case of a symmetrically confined isothermal circular cylinder in a plane channel. Details about the numerical solution, validation of the algorithm and the grid employed can be found elsewhere [36,37].…”
Section: Numerical Solutionmentioning
confidence: 99%
“…The effect of confinement on the vortex-shedding instability The effect of confinement on the vortex shedding in the wake of a two-dimensional cylinder placed inside a channel has been described in the literature, (see e.g. Chen, Pritchard & Tavener 1995;Sahin & Owens 2004;Camarri & Giannetti 2007;Biancofiore, Gallaire & Pasquetti 2011). Constraint of the confining walls has a stabilizing effect, due to the interaction between the cylinder wake and the wall boundary-layer vorticity.…”
Section: Validationmentioning
confidence: 99%